Summary of the 2024 professionals in nutrition for exercise and sport "10 questions/10 experts" session—hot topics for the Paris Olympic Games - Wardenaar, F., C.; Clark, N.; Stellingwerff, T.; Siegler, J.; Saunders, B.; Dolan, E.; Wilson, P., B.; Hawley, J., A.; Fuchs, C., J.; Aussieker, T.; Phillips, S., M.; Manore, M.; et al. (International Journal of Sport Nutrition and Exercise Metabolism, 2024)
This article provides a recap of the 10 Questions/10 Experts session at the 2024 American College of Sports Medicine Annual Meeting. Each of the speakers considered the validity of common "myths," while providing evidence-based opinions to support, or, bust, myths addressing the following questions: (1) Would 100 g/hr of carbohydrate be advisable for the Olympic Cycling Road race? (2) Is there an advantage in the marathon of ingesting bicarbonate as a hydrogel product? (3) Can genotyping be used to individualize caffeine supplementation in football? (4) Should low fluid consumers drink more to improve 1,500-m track performance? (5) Do urinary markers of dehydration predict poor basketball performance? (6) Do placebo effects influence 10-km track performance? (7) Should combat athletes make weight using glucagon-like peptide-1 receptor agonists? (8) Would crushed ice ingestion help tennis umpires make better decisions in the heat? (9) Are collagen supplements useful to reduce tendon and ligament injuries in volleyball? and (10) Should female athletes plan their training and diet according to their menstrual cycle? This article describes the content of each of the presentations including the most important outcomes and conclusions drawn by the presenters.